When Mosquito HV bites Biomark HD: An automated workflow for high-throughput qPCR - Harshitha Shobha Manjunath; Mahesh Kumar Reddy Kalikiri; Basirudeen Syed Ahamed Kabeer; Sara Tomei (SLAS Technology, 2022)
Automation solutions can significantly improve sample processing efficiency and can be of particular help in core facility settings. Centralized core facilities are being established world-wide aimed at strengthening institutions’ clinical and research enterprises and at addressing the need to process large volumes of samples on expensive cutting-edge technologies in a limited time. High-throughput qPCR profiling is a service offered by most genomics facilities. Several platforms have been developed to process large numbers of samples in a short time, including the Fluidigm Biomark HD, which has also been proved useful to increase the SARS-CoV-2 testing capacities. Several automation systems are currently available to miniaturize volumes and improve bioanalytical workflows, including the SPT Labtech Mosquito HV system. Here we have applied the Mosquito HV platform for the automation of the sample preparation of the Fluidigm gene expression workflow. We have successfully automated the pre-amplification and exonuclease cleanup steps with the aim of reducing manual error and sample processing time. We show consistency in the expression of reference genes when assessing pooled RNA control samples for the manual and automated workflows of Fluidigm gene expression profiling.